Thrombin Generation and Platelet Function in ICU Patients Undergoing CVVHD Using Regional Citrate Anticoagulation - Wiegele, Marion; Infanger, Lukas; Lacom, Conrad; Koch, Stefan; Baierl, Andreas; Schaden, Eva (Frontiers in Medicine, 2021)
Background To investigate pro- and anticoagulant alterations in uremic critically ill patients prior to and during continuous renal replacement therapy. In addition to the conventional thrombin generation assay (TGA), we performed a thrombomodulin-modified variant to better elucidate procoagulant imbalances. Platelet function was determined via multiple electrode aggregometry (MEA) to round off hemostatic analysis. Methods We prospectively enrolled patients at surgical intensive care units (ICU) with acute kidney injury undergoing continuous veno-venous hemodialysis using regional citrate anticoagulation. TGA and platelet function testing were performed at baseline (≤ 12 hours prior to continuous renal replacement therapy) and on three consecutive days (day A – C) of extracorporeal therapy. Results We did not observe significant changes in thrombin generation after start or during renal replacement therapy. Ratios of endogenous thrombin potential in patients were significantly increased (p<0.001) compared to standardized plasma of healthy donors confirming the assumed procoagulant alterations in ICU patients. Test results of the conventional TGA differed significantly (p<0.05) from those of the thrombomodulin-modified assay. The area under the curve remained below MEA reference values during the entire observation period, indicating a persistent reduction in platelet function. Conclusion In summary, in-depth analysis using standard and modified TGA, as well as calculation of endogenous thrombin potential (ETP) ratios, revealed no further aggravation of the procoagulatory shift in the critically ill patient during CVVHD using regional citrate anticoagulation. MEA ruled out the potential impact of platelets.